RAMSAR city accreditation: ways on improving sustainability of Wetlands - Ibrahim, Irini; Abu Hanifah, Norha; Hashim, Normawati; Mustafa, Maizatun; Loh, Ing Hoe (2017)
The Ramsar City Accreditation has been described in the Conference of Parties (COP 12) by way of Resolution XII.10 in Uruguay in 2015. The objectives of the accreditation are to assist cities, Contracting Parties and stakeholders in promoting awareness and also to support for the wise use and conservation of wetlands and to perform sustainable development initiatives. The accreditation encourages and support cities that are familiar to Wetlands of International Importance, but also other wetlands to establish a positive relationship with the wetlands through increased participation and awareness and consideration of the wetlands in local planning and decision making. The accreditation is also intended to act as models for the study, demonstration and promotion of Ramsar Convention's objectives, approaches, principles and resolutions. This paper highlights the significance of the Ramsar City Accreditation and ways on improving sustainability of wetlands. The benefits, challenges and opportunities for developing the accreditation are also discussed.